Study on Low Flow Rate Operating Characteristics of Hot Waxy Crude Oil Pipelines Based on an Unsteady-State Calculation Method. (19th May 2014) - Yu, Pengfei; Zhang, Jinjun; Yu, Bo; Wang, Yi; Yu, Guojun
Abstract : Hot crude oil pipeline operated at low flow rate might work in an unstable state, where the friction loss continuously increases with the decreasing flow rate. This will lead to harmful flow stagnation and needs proper management. In this paper, the unsteady-state thermal-hydraulic behavior of the coupled pipeline-pump system is investigated by adopting an unsteady-state numerical model instead of the traditional steady-state model. The new model considers the impacts of the heating strategies, initial operating conditions, and pump characteristics on the pipeline characteristics at low flow rate. Through obtaining the transient characteristics of the flow rate and friction loss, the stable and unstable working ranges are distinguished and critical flow rate is calculated. It is shown that the transient characteristics at low flow rate can be classified into three categories. (1) The flow rate keeps constant for the initial period and then decreases continuously while the friction loss increases monotonously. (2) The flow rate is constant while the friction loss increases firstly and then stays stable. (3) The flow rate maintains constancy while the friction loss increases firstly and then decreases to a final stable level. Besides, it can be concluded that the critical flow rate calculated by the unsteady-state method is recommended with preheating before the flow rate drop.